PENGARUH TINGKAT PERTUMBUHAN PERUSAHAAN, TINGKAT PENJUALAN DAN STRUKTUR ASSET TERHADAP RASIO SOLVABILITAS (STUDI KASUS PADA PT. BANK TABUNGAN PENSIUNAN NASIONAL SYARIAH) - Ira Amalia Khairunnisa; Marliyah Marliyah; Tuti Anggraini (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to analyze the effect of the company's growth rate, sales level and asset structure on the solvency ratio at PT. Sharia National Pension Savings Bank for the 2018-2022 period. The sample used is monthly report data for the 2018-2022 period. This study uses a quantitative method with multiple linear regression analysis. Based on the results of the study, it shows that the company's growth rate (X1) has a significant and negative effect on the solvency ratio at Bank BTPN Syariah. The level of sales (X2) has a significant and positive effect on the solvency ratio at Bank BTPN Syariah. Asset structure (X3) has no significant and negative effect on solvency. Keywords: solvency ratio, asset structure, company growth rate, sales level.